A Review of the Effectiveness of Acceptance and Commitment Therapy on Symptoms and Outcomes of Irritable Bowel Syndrome - Azizi Ziabar, Leila Sadat; Fakharian Moghaddam, Sara (Health Nexus, 2025)
The present study was conducted to review the effectiveness of Acceptance and Commitment Therapy (ACT) on the symptoms and outcomes of Irritable Bowel Syndrome (IBS). This review study examined the available literature on Acceptance and Commitment Therapy and Irritable Bowel Syndrome from 2000 to 2024 in both Persian and English languages. The keywords "therapy," "acceptance and commitment," "acceptance and commitment therapy," and "irritable bowel syndrome" were searched in reputable databases such as Science Direct, Wiley, PubMed, SID, and Magiran. A total of 25 articles addressing the effectiveness of Acceptance and Commitment Therapy on the symptoms and outcomes associated with Irritable Bowel Syndrome were identified. The results of these studies indicated that group-based or individual ACT interventions positively affected various aspects, including symptom severity, pain intensity, disease perception, immune function, body image, blood cortisol levels, treatment adherence, stress, anxiety, depression, rumination, cognitive flexibility, irrational beliefs, emotional regulation, schemas and emotional processing, experiential avoidance, sleep quality, hope, social capital, life satisfaction, psychological well-being, and quality of life in patients with IBS. The findings of this study suggest that Acceptance and Commitment Therapy can be utilized alongside pharmacotherapy and dietary modifications to alleviate symptoms and outcomes of Irritable Bowel Syndrome.